Edukasi dan Pemberdayaan Perempuan dalam Deteksi Dini dan Pencegahan Kanker Payudara (Lembaga Pengembangan Kinerja Dosen, 2026)
Breast cancer is one of the most prevalent cancers among women and remains a major public health concern due to late detection and limited awareness of early prevention. Community empowerment through health education plays a crucial role in improving knowledge and early detection practices. This community service activity aimed to enhance women’s knowledge and skills related to breast cancer prevention and early detection through breast self-examination (BSE). The activity employed a participatory educational approach, including health education sessions, demonstrations, and hands-on BSE practice. Participants were women aged 20–60 years from the community. Evaluation was conducted using pre-test and post-test questionnaires and direct observation of BSE practice. The results indicated a significant improvement in participants’ knowledge and ability to correctly perform BSE following the intervention. These findings suggest that structured, community-based education and empowerment programs are effective in increasing awareness and promoting early detection behaviors for breast cancer. Continuous implementation of such programs is recommended to support breast cancer prevention efforts and improve women’s health outcomes.